Prospective, double‐blind, randomized clinical trial comparing an ERAS pathway with ketorolac and pregabalin versus standard of care plus placebo during live donor nephrectomy for kidney transplant. Issue 6 (28th January 2019) - Campsen, Jeffrey; Call, Tyler; Allen, Chelsea McCarty; Presson, Angela P.; Martinez, Eryberto; Rofaiel, George; Kim, Robin D.
Abstract : Opioid exposure is a concern after live donation for kidney transplant. We theorized that an enhanced recovery after surgery pathway (ERAS) using pregabalin preoperatively to desensitize nerves followed by the nonsteroidal anti‐inflammatory drug ketorolac, during and after surgery, can control pain, thus requiring less perioperative narcotics. The aim of this study was to determine if the use of a nonopioid analgesic ERAS protocol for donor nephrectomies could decrease the use of narcotics without an increase in complications compared with standard of care (SOC). This is a single‐center, prospective, double‐blind, randomized clinical trial involving a total of 62 patients undergoing nephrectomy for live donor kidney transplant. Length of hospital stay (LOS) was significantly reduced by 10% in the ERAS group versus the SOC‐plus‐placebo group. Morphine dose equivalents were significantly reduced by 40% in the study group versus the SOC‐plus‐placebo group. The use of this nonopioid analgesic ERAS pathway for donor nephrectomies decreased the use of narcotics without an increase in complications compared with SOC. There was significantly reduced LOS and less narcotic use in the study group versus the SOC‐plus‐placebo group. (ClinicalTrials.gov registration number: NCT03669081). Abstract : This double‐blind, randomized study evaluates an enhanced postsurgery recovery pathway consisting of ketorolac and pregabalin, with the aim of lowering postoperative opioid use in live kidney donors.